Association between the emotional status of family caregivers and length of stay in a palliative care unit: A retrospective study. Issue 6 (11th June 2015) - Kim, Seon Hee; Hwang, In Cheol; Ko, Ki Dong; Kwon, Young Eun; Ahn, Hong Yup; Cho, Nan Young; Kim, Seung Jin
ABSTRACT: Objective: Several factors associated with referral time to hospice and/or palliative care services have been identified, but there is no literature on the association between these services and the emotional status of the family caregivers (FCs). This article is intended to address that issue. Method: A semistructured interview was employed to collect data for a retrospective cohort study. The primary FCs of terminally ill cancer patients were interviewed at the time of the patient's referral to the palliative care unit. Interview data were combined with patients' medical record data for our analysis. The emotional status of the FCs was categorized into one of three groups according to their responses to the anticipated death of their family member: acceptance, anxious/depressed, and denial/angry. A Cox proportional hazard model was used to examine and identify the factors related to the length of stay (LOS) in the palliative care unit. Results: A total of 198 patient–FC pairs were identified. The median LOS was 18 days. A multivariate analysis with adjustment for potential variables revealed significant differences in LOS according to cancer type and time since cancer diagnosis. The denial/angry FC category was independently associated with a shorter LOS (vs. acceptance, adjusted hazard ratio (aHR) 2.11; 95% confidence interval ( CI ), 1.11–4.03). Significance of Results: We found that terminally ill cancer patients who were referred late had FCs who were in denial or were angry about the anticipated death of their loved one. The emotional status of FCs should be considered when patients with terminal cancer are referred to palliative care.